Leveraging innovativeness for enhanced small and medium enterprises performance: the moderating role of learning orientation - Gurpreet pal Kaur; Harpreet Singh Bedi; Harish Saini (Journal of Innovation and Entrepreneurship)
Abstract The study aims to assess the innovativeness–business performance relationship by considering learning orientation as moderator. Data has been gathered from 413 Small and Medium Enterprises (SMEs) in Punjab, India, using a quantitative study design. Structural equation modelling has been used to evaluate the proposed relationships. The results reveal that innovativeness and business performance have a positive relationship, which is moderated by learning orientation. The findings of this study attempts to encourage SMEs for nurturing the culture of continuous learning and experimentation. SMEs may enhance their performance and competitiveness in fast-paced business environments by being innovative and learning-oriented. Theoretical and practical implications are considered, in addition to limitations and future research directions.